Factors affecting students' interest in learning speaking skills at Finance and Accounting Department, Hoa Binh University = Những yếu tố ảnh hưởng đến sự hứng thú trong việc học kỹ năng nói của sinh viên khoa Tài chính kế toán trường Đại học Hòa Bình. M. - Phạm, Thị Vân (University of Languages and International Studies, 2017)
It is considered that speaking is given the most important account of four skills in learning English. In comparison with other skills, speaking will be used most often in our life. However, in reality, studentsatFinance and Accounting Department,Hoa Binh University are not much interested in speaking English.The study focuses on the factors affecting students' interest in learning speaking skills atFinance and Accounting Department,Hoa Binh University. Once the problems have been identified, suggestions to improve the situation of teaching and learning English for teachers and students at Finance and Accounting Department,Hoa Binh Universitywould be made. In this paper, the researcher uses “survey questionnaire” for 150 students at Finance and Accounting Department and seven teachersteaching the students